Caspian Tern Response to Managed Reductions in Nesting Habitat. (25th August 2020) - Schniedermeyer, Ethan; Roby, Daniel D.; Lyons, Donald E.; Suzuki, Yasuko; Collis, Ken
ABSTRACT: Predation on smolts by Caspian terns ( Hydroprogne caspia ) has been identified as a factor limiting the restoration of some populations of anadromous salmonids ( Oncorhynchus spp.) from the Columbia River basin that are listed under the U.S. Endangered Species Act. Implementation of a management plan to reduce numbers of Caspian terns nesting at the 2 largest colonies in the Columbia Plateau region of Oregon and Washington, USA, began in 2014 and is ongoing. We investigated the response of Caspian terns during 2014–2016 to reductions in nesting habitat at these 2 colonies. Management prevented terns from nesting at both colonies, and the estimated numbers of nesting pairs in the region declined significantly from a mean of 877 pairs during premanagement to 769 and 675 pairs in 2015 and 2016, respectively. The management objective of reducing numbers of nesting terns in the Columbia Plateau region to ≤200 breeding pairs was not achieved during the first 2 years of full implementation of the plan. Regional nesting success did not decline significantly following the initiation of management, and remained at levels considered sufficient to sustain the regional subpopulation. Despite the species' capacity for long‐distance breeding dispersal, the majority of displaced terns exhibited stronger than expected philopatry to the Columbia Plateau region. Analysis of resightings of banded terns indicated that most (>80%) terns that nested in the Columbia Plateau region premanagement returned to the region in 2015 and 2016, but the proportion that returned as breeders decreased while the proportion that returned as nonbreeding floaters increased compared with premanagement. The proportion of banded terns that were unobserved also increased during management years, suggesting that more terns became floaters in the Pacific Flyway and went unobserved because they were prospecting and foraging in locations or regions where there was little or no monitoring. The unexpectedly high regional philopatry exhibited by terns during management was likely a reflection of the low availability of suitable alternative nesting habitat outside the region. Most terns that remained in the region displayed considerable flexibility in nest site selection by nesting either at a previously smaller, intermittently successful breeding colony or at a small new colony where nesting activity had not previously been recorded. As long‐lived seabirds, Caspian terns may integrate information regarding nesting success over several years before choosing to change nesting locations, longer than the 2 years of this study, especially if alternate locations are distant or intermittently available, or a history of nesting at multiple locations exists within the region. © 2020 The Wildlife Society.  : We evaluated the response of Caspian terns ( Hydroprogne caspia ) to non‐lethal management intended to eliminate nesting habitat at the two largest Caspian tern colonies in the region and thereby reduce predation on ESA‐listed juvenile salmonids ( Oncorhynchus spp.) in the Columbia Plateau region of Washington and Oregon, USA. Following three breeding seasons of management, both Caspian tern colonies were vacant and the regional breeding population had declined by 23%, but Caspian terns exhibited greater than expected philopatry to the Columbia Plateau region and most terns (>80%) returned, some as non‐breeding floaters, apparently because of limited nesting opportunities outside the region.